Mixing and capping techniques for activated carbon based sediment remediation – Efficiency and adverse effects for Lumbriculus variegatus. (1st May 2017) - Abel, Sebastian; Nybom, Inna; Mäenpää, Kimmo; Hale, Sarah E.; Cornelissen, Gerard; Akkanen, Jarkko
Abstract: Activated carbon (AC) has been proven to be highly effective for the in-situ remediation of sediments contaminated with a wide range of hydrophobic organic contaminants (HOCs). However, adverse biological effects, especially to benthic organisms, can accompany this promising remediation potential. In this study, we compare both the remediation potential and the biological effects of several AC materials for two application methods: mixing with sediment (MIX) at doses of 0.1 and 1.0% based on sediment dw and thin layer capping (TLC) with 0.6 and 1.2 kg AC/m 2 . Significant dose dependent reductions in PCB bioaccumulation in Lumbriculus variegatus of 35–93% in MIX treatments were observed. Contaminant uptake in TLC treatments was reduced by up to 78% and differences between the two applied doses were small. Correspondingly, significant adverse effects were observed for L. variegatus whenever AC was present in the sediment. The lowest application dose of 0.1% AC in the MIX system reduced L. variegatus growth, and 1.0% AC led to a net loss of organism biomass. All TLC treatments let to a loss of biomass in the test organism. Furthermore, mortality was observed with 1.2 kg AC/m 2 doses of pure AC for the TLC treatment. The addition of clay (Kaolinite) to the TLC treatments prevented mortality, but did not decrease the loss in biomass. While TLC treatments pose a less laborious alternative for AC amendments in the field, the results of this study show that it has lower remediation potential and could be more harmful to the benthic fauna. Graphical abstract: Highlights: Activated Carbon (AC) efficiently reduces PCB bioaccumulation from sediment to biota. Mixing sorbent particles into the sediment and thin layer caps are both effective. Adverse effects can reach severe levels, especially under thin layer caps. Microvilli damages in Lumbriculus variegatus were observed after AC exposure. Adding Clay to the AC particles before application can reduce the adverse effects.